2004
DOI: 10.21061/jcte.v20i2.637
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Postsecondary Marketing Student Performance on Computer- Based and Handwritten Essay Tests

Abstract: The purpose of this study was to determine if there were differences in postsecondary marketing student performance on essay tests based on test format (i.e., computer-based or handwritten

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…In fact, all students, regardless of disability status or sex, wrote longer essays in the WP condition. This finding is supported by previous research that found students wrote longer essays on a WP than by hand (Gregg et al, 2007;Russell et al, 1999;Truell, Alexander & Davis, 2004). Therefore, a WP appears to benefit all students in writing production.…”
Section: Discussionsupporting
confidence: 83%
“…In fact, all students, regardless of disability status or sex, wrote longer essays in the WP condition. This finding is supported by previous research that found students wrote longer essays on a WP than by hand (Gregg et al, 2007;Russell et al, 1999;Truell, Alexander & Davis, 2004). Therefore, a WP appears to benefit all students in writing production.…”
Section: Discussionsupporting
confidence: 83%
“…The findings of this study indicated that both teachers and learners were enthusiastic to engage the software program in mathematics MCQ assessment, and developing more such programs may change the face of assessment in Zimbabwe. According to Truell, Alexander and Davis (2004), computer-based assessments by default offer assessment mode benefits to candidates, such as single-item display and good visualisation, which, to some extent, boost their performance. A computer heightens learners' interest in test-taking (McIntosh & Stacey, 2000), which in turn can help to reduce mathematics-phobia amongst learners.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, according to Clariana and Wallace (2002), one-item display which features most in computer-based assessment gives greater focus and closure on individual test items, which in turn increases concentration. Such observations are insignificant given that computer-based MCQ administration yielded no significant difference in candidates' performance based on test format (Truell, Alexander and Davis, 2004).…”
Section: Theoretical Frameworkmentioning
confidence: 89%
See 1 more Smart Citation